2019
DOI: 10.25083/rbl/24.6/1097.1106
|View full text |Cite
|
Sign up to set email alerts
|

An investigation for the development of whey-based probiotic beverages

Abstract: Whey is the one of the byproducts of cheese-making. Due to the high nutrient content of whey, it is being used to prepare many different products. Probiotic bacteria have been used to develop new whey containing beverages so new generation-products can be produced which influence the human health positively. The aim of this study was to define the growth and survival of probiotic microorganisms, Lactobacillus plantarum AA1-2 and Saccharomyces boulardii, in whey. The whey was inoculated and fermented with L. pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The results of the present study showed that the chemical composition of the beverages was comparable to that of whey and whey-based beverages [18,19,23,25]. The high moisture values of the whey beverages were expected due to the high percentage of whey used in the formulation of the product and are in line with acceptable values for liquid yogurts (maximum 91.5% moisture).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the present study showed that the chemical composition of the beverages was comparable to that of whey and whey-based beverages [18,19,23,25]. The high moisture values of the whey beverages were expected due to the high percentage of whey used in the formulation of the product and are in line with acceptable values for liquid yogurts (maximum 91.5% moisture).…”
Section: Discussionsupporting
confidence: 74%
“…A distinction is made between sweet whey, which is obtained by the addition of rennet (pH = 6-7), and acid whey, when coagulation occurs through the action of acid (pH < 5) [17]. This by-product contains about 50% of the nutrients/dry matter of milk [18], including lactose (70-80% DM), proteins (9% DM), minerals (8-20% DM) and other minor components [17,19]. The content of lactose and other nutrients makes whey a potential raw material for the development of probiotic microorganisms that enable the production of fermented beverages [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the carbonation process can result in probiotic death (Ansari et al ., 2013). Previous studies are mainly related to the processing of probiotic carbonated fermented whey dairy beverages (Shah and Prajapati, 2014; Sağlam et al ., 2019) because the fermentation step helps in increasing the probiotic viability. As far as the authors know, there are no reports on probiotic carbonated non-fermented whey dairy beverages based on a mixture of whey and milk.…”
mentioning
confidence: 99%
“…In addition to the dairy‐based functional products containing probiotics sold on the market, various studies have been conducted to develop new products. In some of these studies, different milk components such as whey and different probiotics were used to develop products (Saglam et al., 2019 ; Skryplonek et al., 2019 ), while in others, various fruit juices, concentrates, and/or pulps and cereals were added to whey and fermented with probiotics. In some studies, milk is also included in these mixtures (De Andrade et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%